2022
DOI: 10.3389/fimmu.2022.970950
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A-mediated molecular subtypes characterize the hallmarks of tumor microenvironment and guide precision medicine in triple-negative breast cancer

Abstract: Currently, breast cancer (BRCA) has become the most common cancer in the world, whose pathological mechanism is complex. Among its subtypes, triple-negative breast cancer (TNBC) has the worst prognosis. With the increasing number of diagnosed TNBC patients, the urgent need of novel biomarkers is also rising. Cyclin-dependent kinase inhibitor 2A (CDKN2A) has recently emerged as a key regulator associated with ferroptosis and cuproptosis (FAC) and has exhibited a significant effect on BRCA, but its detailed mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 79 publications
2
17
1
Order By: Relevance
“…For example, although transient cell senescence, which is indicative of functional p53 signaling in response to many forms of DNA damage, is recognized as a tumor suppressor mechanism, persistent senescence accompanied by p53 inactivation would promote a senescence-associated secretory phenotype (SASP), which stimulates the secretion of numerous proinflammatory cytokines and growth factors that may modulate the epigenome and disrupt normal tissue structure and function [ 20 ]. In our study, we indeed observed a significantly higher expression of CDKN2A , a cell senescence marker, in basal-like tumors as compared to tumors of other subtypes, a finding that we replicated in TCGA breast (Additional file 3 : Figure S3) and was reported by Cheng et al using TCGA data [ 21 ]. In addition, oncogene-induced senescent cells could also re-enter the cell cycle and present with a much higher tumor initiation potential (enhanced cancer-cell stemness), resulting in a highly aggressive tumor phenotype [ 22 ], such as basal-like tumors.…”
Section: Discussionsupporting
confidence: 87%
“…For example, although transient cell senescence, which is indicative of functional p53 signaling in response to many forms of DNA damage, is recognized as a tumor suppressor mechanism, persistent senescence accompanied by p53 inactivation would promote a senescence-associated secretory phenotype (SASP), which stimulates the secretion of numerous proinflammatory cytokines and growth factors that may modulate the epigenome and disrupt normal tissue structure and function [ 20 ]. In our study, we indeed observed a significantly higher expression of CDKN2A , a cell senescence marker, in basal-like tumors as compared to tumors of other subtypes, a finding that we replicated in TCGA breast (Additional file 3 : Figure S3) and was reported by Cheng et al using TCGA data [ 21 ]. In addition, oncogene-induced senescent cells could also re-enter the cell cycle and present with a much higher tumor initiation potential (enhanced cancer-cell stemness), resulting in a highly aggressive tumor phenotype [ 22 ], such as basal-like tumors.…”
Section: Discussionsupporting
confidence: 87%
“…In the past, studies have focused on the tumor suppressor gene role of CDKN2A, and mutations of which led to loss of growth control in breast cancer(BRCA) [ 112 ], HNSC [ 113 ] and ovarian cancer cells [ 114 ], but its role in cuproptosis remains to be further investigated. CDKN2A was suggested to be highly expressed in BRCA and LUAD, and in addition, high CDKN2A expression was thought to correlate with immune cell infiltration levels [ 116 , 117 ].…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, excessive deposition of intracellular copper can induce fatty acylated dihydrofatamide s-Acetyltransferase (DLAT) aggregates and affects the TCA cycle, resulting in proteotoxic stress and, consequently, cell death [ 13 ]. Moreover, since other studies have suggested the close relationship between cuproptosis and breast cancer [ 25 ], we speculate that the induction of cuproptosis in breast carcinomas may become a new avenue for treating breast cancer.…”
Section: Discussionmentioning
confidence: 81%